2005
DOI: 10.1016/j.jpainsymman.2005.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Symptom Assessment in Russia: Validation and Utility of the Russian M. D. Anderson Symptom Inventory

Abstract: This multicenter cross-sectional study (n=226) validated the Russian-language M. D. Anderson Symptom Inventory (MDASI-R) in Russian cancer patients with hematological malignancies or solid tumors. The Russian-language Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36-R) also was used for validation. Factor analysis found three underlying constructs for symptom items--general, treatment-related, and affective symptoms--with Cronbach alphas of 0.86, 0.68, and 0.90, respectively. Convergent validity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 21 publications
6
55
1
5
Order By: Relevance
“…11,17 The addition of anorexia to this cluster has also been reported, as has the addition of dyspnea. 18,29 The association between fatigue/malaise/lethargy and dehydration has also been reported previously. 28 These findings are reassuring and confirm the clinical relevance of these severe adverse event clusters in the management of symptoms.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…11,17 The addition of anorexia to this cluster has also been reported, as has the addition of dyspnea. 18,29 The association between fatigue/malaise/lethargy and dehydration has also been reported previously. 28 These findings are reassuring and confirm the clinical relevance of these severe adverse event clusters in the management of symptoms.…”
Section: Discussionsupporting
confidence: 66%
“…[9][10][11] In recent years, symptom clusters have been evaluated across a variety of cancers, [12][13][14] with several studies in breast cancer, [15][16][17] lung cancer, [18][19][20] and non-Hodgkin lymphoma 21 and across multiple cancer sites. [22][23][24][25][26][27][28][29][30][31][32] Each of these studies prospectively collected patient-reported symptoms. Although having patient-reported outcomes is important for the understanding of symptom clusters, they are not always collected in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and validation process for the MDASI have been reported elsewhere. 8,11 Patients were asked to complete the MDASI at baseline before starting chemoradiation, weekly during chemoradiation, and monthly after the completion of chemoradiation. The first followup after treatment was coincident with the restaging CT scan (around day 94 from initiation of therapy).…”
Section: Assessment Of Symptoms and Functional Impairmentmentioning
confidence: 99%
“…The MDASI was linguistically and psychometrically validated in Japanese (8) , Greek (9) , Chinese (10) , Russian (11) , Korean (12) , Thai (13) , Filipino (14) , Arabic (15) and French (16) . However, in Brazil this instrument had only linguistic validation (5) , which demonstrated the need for its psychometric validation.…”
Section: Introductionmentioning
confidence: 99%